Convenient Synthesis of 5-Arylidene-2-imino-4-thiazolidinone Derivatives Using Microwave Irradiation - Sarkis, Manal; Tran, Diem-Ngan; Dasso Lang, Maria Chiara; Garbay, Christiane; Braud, Emmanuelle (Synlett, 2014)
A concise approach for the preparation of 5-arylidene-2-imino-4-thiazolidinone derivatives is described. Structurally diverse amines, isothiocyanates, aldehydes, and chloroacetyl chloride were combined under microwave irradiation to afford new 5-arylidene-2-imino-4-thiazolidinone derivatives. The one-pot synthesis involves the in situ formation of a thiourea followed by reaction with chloroacetyl chloride and an aldehyde to generate the target compounds.
Keywords: 5-arylidene-2-imino-4-thiazolidinone; thiourea; microwave irradiation; multicomponent reaction; Knoevenagel condensation